TRAFFICKING OF WOMEN IN SOUTH ASIA - Cheema, Iqtidar Kramat (Journal of Research in Humanities, 2023)
Trafficking in women and enforced prostitution are forms of violence for profit to which a substantial number of women are subjected. While trafficking is more prevalent in the case of foreign women being brought into the country, internal trafficking of Pakistani women is said to be on the rise, though there is insufficient information about it. Enforced prostitution of girls from lower-income backgrounds has always been in existence, with very few being able to escape from the net even if they wish to do so. However, very little has been done to effectively stem the practice or to rehabilitate the victims of the crime. In fact, all legislation and legal action has been focused on the victims of the crime, with little attention directed at the pimps and agents who profit from it or the prostitute-seekers, who are the persons responsible for the existence and growth of the practice.